Looking for the elusive alpha tin phase - Dr Daniela Di Martino; Dr Antonella Scherillo; Professor Giuseppe Gorini; Dr Ivan da Silva Gonzalez; Dr Enrico Perelli Cippo (ISIS Facility, 2019)
The characteristics of metal alloys have always been considered crucial for the sound quality of organ pipes. Tin-rich materials were studied for conservation issues, like the so-called “tin pest” -a consequence of a tin crystal structure change. “Tin pest” is indeed an allotropic transformation of tin, from beta-phase (tetragonal structure) to alpha-phase (diamond-cubic structure). This phase transformation, spontaneous below 13.2 °C, is strongly accelerated by lower temperatures. Recently, we studied a wide set of tin-based pipe fragments but no alpha-phase was found. We thus propose to study a real and different commercial specimens, as a function of the temperature, after 24 hours at -50°C. Our measurements want to infer information on the degradation process, in order to make an assessment of neutron techniques as a diagnostic tool the conservation of organ pipes.
Keywords: STFC ISIS Neutron and Muon Data